Marketing Strategy Analysis Using Soar Method on Confetti Project - Lailatul Hijrah; Trisda Derama (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Invitation printing services are one of the services that are growing rapidly at this time due to the increasing rate of weddings in Indonesia. In 10 sub-districts in Samarinda the total number of marriages reached 3,344 married couples. One of the invitation printing services in Samarinda, namely the Confetti Project. With the rapid development of this industry, there is fierce competition, so strategic planning/analysis is needed to help survive in this industry. With the aim of identifying the best marketing strategy for the Confetti Project. The method in this research is descriptive qualitative with SOAR analysis approach. Data was collected by collecting information about marketing strategies by conducting interviews and direct observation. The results obtained are alternative marketing strategies obtained from the SOAR matrix.